Risk of Cardiovascular Disease among Diabetic Patients in Manipur, Northeast India. (26th May 2014) - Tungdim, Mary Grace; Ginzaniang, T.; Kabui, G. Poufullung; Verma, Deepali; Kapoor, Satwanti
Abstract : Atherosclerotic cardiovascular disease is the major cause of premature mortality in patients with type 2 diabetes. The present study was conducted to assess cardiovascular risk among diabetic patients of Northeast India. The present cross-sectional study included 81 diabetic patients (39 males and 42 females) aged 36–74 years from the district Imphal of Manipur, Northeast India. Sex-specific Framingham general cardiovascular risk prediction equations were used to calculate the 10-year risk for cardiovascular disease. The probable risk factors were determined by cross-tabulation of cardiometabolic parameters with the 10-year cardiovascular risk level. Males were found to be at higher risk of developing CVD in the future as compared to females with a discernible accumulation of adverse cardiovascular risk factors among them. 38.3% patients were at high risk, 37.0% at moderate risk and 24.7% at low risk for developing CVD in the next 10 years. Systolic blood pressure, total cholesterol, triglyceride, and smoking contributed significantly to high degree of cardiovascular risk. Presence of cardiovascular risk factors among diabetic patients at diagnosis accentuates the need of intensive management of cardiovascular complications, taking into consideration the traditional dietary pattern of the population.